2015
DOI: 10.1007/978-94-017-9585-2_12
|View full text |Cite
|
Sign up to set email alerts
|

The Riddle of Attractiveness: Looking for an ‘Aesthetic Sense’ Within the Hedonic Mind of the Beholders

Abstract: Beauty, my dear Sir, is not so much a quality of the object beheld, as an effect in him who beholds it. Spinoza, 1674Spinoza, (1901, Letter to Hugo Boxel Abstract Darwin conceived the theory of sexual selection in order to explain beauty in animal Kingdom. He hypothesised that most of the male ornaments had been developed to correspond to a female 'sense of beauty'. His successors developed a theory of mate choice in which the aesthetic sense was left out. The male sexual ornaments were considered as salient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 79 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…Historically in evolutionary biology, the mechanisms that link stimulus and behavior have been modeled using simplified frameworks that ignore the complexity of brain processes [112]. This simplified approach has been motivated possibly by a fear of anthropomorphism, but also because brain processes were once considered elusive and unpredictable (but see [113,114]).…”
Section: A Broader Outlookmentioning
confidence: 99%
“…Historically in evolutionary biology, the mechanisms that link stimulus and behavior have been modeled using simplified frameworks that ignore the complexity of brain processes [112]. This simplified approach has been motivated possibly by a fear of anthropomorphism, but also because brain processes were once considered elusive and unpredictable (but see [113,114]).…”
Section: A Broader Outlookmentioning
confidence: 99%
“…Second, live stream viewers’ affective and social integrative gratifications increased when they were watching beauty influencers. Prior studies have well-documented the hedonic value derived from esthetic appreciation, especially when human faces and bodies are involved ( Kreutzer and Aebischer, 2015 ; Swami et al, 2018 ). Moreover, search costs can be economized and sense of loneliness can be mitigated if it is easy to find discussants, with whom live stream viewers are able to share thoughts and feelings about a good-looking streamer, which explains why people happen to favor the most popular stars from an economic perspective ( Adler, 1985 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, photogrammetry was applied in order to evaluate facial attractiveness of females during menstruation and ovulation phases of their sexual cycles. This is to ascertain whether facial beauty/attractiveness maybe deduced as an indicator for ovulation; since unlike other animals that has visible signs of ovulation [14,15], visible indicators of ovulation is not fully elucidated. Considering the preference of the males which tilts towards the facial picture during the ovulatory phase in this study, it was suggested that enhanced facial beauty/attractiveness could be a biomarker of ovulation as there was positive significant correlation of facial proportions of the subjects during the various phases of their sexual cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Reports suggest that females are more attractive in the fertile phase of their sexual cycle [12,13]: in animals; redness of waist, colourful plumes,etc. are biomarker of ovulation that makes them attractive as well as makes mating possible [14,15]. In humans reliable indicators of ovulation is not fully explained.…”
Section: Introductionmentioning
confidence: 99%